Renewable energy smart sensing system monitoring for off-grid vulnerable community in Colombia. Issue 1 (1st January 2021) - Colmenares-Quintero, Ramón Fernando; Valderrama-Riveros, Oscar Camilo; Macho-Hernantes, Fernando; Stansfield, Kim E.; Colmenares-Quintero, Juan Carlos
Abstract: The implementation of renewable energy is a necessity nowadays and like any other technology involves challenges and opportunities to achieve. The main objective of our projects in an off-grid vulnerable community in Colombia is to design a smart grid to control the power grid, but also to understand the grid behavior and the actors (generators and consumers) for which a smart monitoring system must be implemented in the initial phase of these initiatives. This work proposes the design of a smart monitoring sensing system to gather information on both the status of electrical variables (i.e., power, current, voltage, reactive energy, and power factor) and environment variables (i.e., temperature, solar radiation, GPS, humidity, and atmospheric pressure) for an off-grid renewable energy system fit for a vulnerable community in Colombia. The system was created as a web-app that allows multiplatform access and allows scalability for large numbers of generators and loads. Finally, the system offers flexibility to exploit different sensors or hardware to measure the variables since it only reads the information from the data base.